Strategi Kepala Sekolah dalam Meningkatkan Mutu Pendidikan Agama Islam di SMAN 07 Kepahiang - Yova Atika; Pitrawana Pitrawana; Sri Hartati (Jurnal Bintang Pendidikan Indonesia, 2024)
The principal's leadership strategy plays a central role in shaping the success of improving the quality of education in a school. The aim of this research is to reveal the strategies used by school principals to improve the quality of Islamic religious education at SMA Negeri 7 Kepahiang. To achieve the above objectives, this research uses a qualitative methodology using descriptive techniques. The data required for the research effort was obtained through the use of observation, interview, and document analysis techniques. The focus of this research is related to school principals. The results of this research illustrate that there are six strategies that have been implemented by the principal to improve the quality of Islamic religious education at SMA Negeri 7 Kepahiang, including steps such as internal improvement, an effective supervision system, evaluation in the teaching and learning process, strengthening teacher discipline, promotion, and improvement of facilities and infrastructure. Thus, the leadership of the school principal is the main element in achieving success in advancing the quality of education.